Aesthetic issues in the design of multimedia virtual exhibition spaces - Chernikov, M.; Vasylieva, O.; Batrak, V.; Shaura, A. (Art and Design, 2025)
The relevance of the study was determined by the digitisation of the museum sector and the growing role of virtual exhibitions in preserving cultural heritage. At the same time, digital technologies create aesthetic challenges that affect the quality of the user experience, making the study of the aesthetics of virtual exhibitions relevant for modern design. The aim of the study was to analyse and identify the main aesthetic problems in the design of digital museum spaces, analyse effective design solutions, and formulate practical recommendations for improving the user experience. The methodological basis of the study was a comparative and visual analysis of various types of virtual exhibition examples, from two-dimensional websites to three-dimensional tours and virtual reality galleries. For an objective analysis, twelve cases of virtual museums were considered, classified according to their presentation format. The results of the study revealed the existence of typical aesthetic problems, such as overloaded or chaotic composition, incorrect use of colours, unadapted typography, mismatched object scales, and ineffective interactivity. These shortcomings lead to a decrease in emotional engagement, cognitive load, and the duration of users’ stay in digital spaces. At the same time, the analysis revealed positive design practices based on a logical structure of space, well-thought-out navigation, harmonious colour schemes, adaptive typography, and interactivity, which increase audience engagement and satisfaction. Platforms that combine multimedia elements with personalised viewing routes and the ability to interact with exhibits proved to be particularly effective. The practical value of the article lies in formulating a general vision of the issue, which will help curators, designers, and developers of virtual exhibitions in the aesthetic optimisation of digital space